Concomitant Nephrotic Syndrome and Cryoglobulinemia in a Case of Malignant Mesothelioma. (28th September 2022) - Nagai, Kei; Tachi, Hiroaki; Inoue, Kohei; Ueda, Atsushi
Abstract : Malignant pleural mesothelioma is rarely associated with nephrotic syndrome. Cryoglobulinemia is found in various pathological statuses, such as hepatitis C virus infection but rarely in malignant neoplasms. We recently encountered a patient with malignant mesothelioma coincident with nephrotic syndrome and cryoglobulinemia in the course of chemotherapy. A 60-year-old man employed as a building painter was diagnosed with malignant mesothelioma by lung biopsy two years earlier and was started on chemotherapy. Nivolumab seemed effective in controlling mesothelioma, but skin immune-related adverse events occurred during the course of treatment. After discontinuation of nivolumab and administration of gemcitabine as an alternative therapy, the patient was referred to a nephrologist because of the subsequent development of edema, renal injury, and proteinuria. Following the investigation, he was diagnosed with nephrotic syndrome and cryoglobulinemia with C4-dominant cold activation. However, a percutaneous renal biopsy could not be performed due to persistent severe cough induced by pleural involvement. The patient died a little over three years after the pathological diagnosis of pleural mesothelioma. Our case had three key features nephrotic syndrome was possibly associated with malignant mesothelioma; cryoglobulinemia occurred in malignant mesothelioma; and concomitant nephrotic syndrome and cryoglobulinemia occurred after chemotherapy. Unfortunately, our rare case lacks a basis in renal pathology or evidence of links between the pathogenesis of malignant mesothelioma, cryoglobulinemia, and nephrotic syndrome. This case does not provide a causal mechanism, but may be worth adding to the case list as one of the rare renal involvement in a patient with malignant mesothelioma.